THE UTILIZATION OF ZAKAT FUNDS FOR THE FREE NUTRITIOUS MEAL PROGRAM: A REVIEW OF FIQH AND NATIONAL ZAKAT REGULATION - Ansori, Moh. Asep Zakariya; Sukendar, Egi Agustian Rahmat (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to examine the juridical aspects of using zakat funds for the Free Nutritious Meal Program (MBG) based on the perspective of zakat jurisprudence (fiqh) and national legislation, particularly Law Number 23 of 2011 concerning Zakat Management. The method used is normative-juridical with a qualitative approach, employing a literature review of primary sources (the Qur'an, hadith, and authoritative fiqh texts) as well as secondary sources (laws and regulations, scholarly articles, and institutional documents related to zakat management). The findings reveal that the allocation of zakat funds for the MBG program is not in accordance with the principles of Islamic law nor with the prevailing positive regulations in Indonesia. This is due to the following reasons: (1) according to sharia, zakat may only be distributed to eight eligible categories (asnaf) as outlined in Surah At-Tawbah: 60, while the MBG program is inclusive and not limited to those categories; (2) participants in the program who are still under the care of financially capable parents do not qualify as poor or needy based on fiqh criteria; and (3) Law No. 23 of 2011 explicitly restricts zakat distribution to the designated asnaf groups. As an alternative, this study recommends the utilization of other social funds such as infaq, sadaqah, or allocations from the state or regional budgets (APBN/APBD), which offer greater flexibility and are not bound by sharia-based recipient restrictions. These findings are expected to serve as a strategic consideration for the government and zakat management institutions in formulating social policies that align with both sharia principles and national regulations.